Influence of Nasal Tip Lifting on the Incidence of the Tracheal Tube Pathway Passing Through the Nostril During Nasotracheal Intubation: A Randomized Controlled Trial. (December 2018) - Kim, Hyerim; Lee, Jung-Man; Lee, Jiwon; Hwang, Jin-Young; Chang, Jee-Eun; No, Hyun-Joung; Won, Dongwook; Choi, Seungeun; Min, Seong-Won
Abstract : BACKGROUND: For safe nasotracheal intubation without middle turbinate injury, the tracheal tube should pass through the lower pathway, which is beneath the inferior turbinate and immediately above the nasal floor of the nostril. The purpose of this study was to assess the influence of nasal tip lifting on the incidence of passing preformed nasal Ring-Adair-Elwyn (RAE) tubes through the lower pathway during nasotracheal intubation. METHODS: Patients were randomly assigned to a "nasal tip lifting group" or a "neutral group." For patients in the nasal tip lifting group, an investigator pulled the nasal tip in a cephalad direction when inserting a preformed nasal RAE tube into the nostril after induction of anesthesia. For patients in the neutral group, a tube was inserted with the nasal tip in a neutral position. The pathway by which the tube passed in each patient was identified using a fiberscope. The incidence of the tube passing through the lower pathway was compared between the 2 groups. The incidence of epistaxis was also evaluated. RESULTS: Eighty-six patients were enrolled and completed the study protocol. The incidence of the tracheal tube passing through the lower pathway was significantly higher in the nasal tip lifting group (79.1%) than in the neutral group (51.2%) (relative risk, 1.55; 95% confidence interval, 1.11–2.15; P = .007). Although the incidence of epistaxis was not different between the groups (18.6% vs 32.6%; P = .138), it was lower when the tracheal tube passed nasal cavity through the lower pathway (14.3%) than the upper pathway (46.7%), regardless of the randomized group with adjustment for potentially confounding variables (odds ratio, 0.19; 95% confidence interval, 0.07–0.54; P = .002). CONCLUSIONS: The nasal tip lifting maneuver helped to guide preformed nasal RAE tubes into the lower pathway during nasotracheal intubation.